Emprego do plasma de descarga por barreira dielétrica (dbd) na inativação de fungos e na superação de dormência em sementes de erythrina velutina willd - Diógenes, Francisco Esio Porto (2017)
Mulungu (E.velutina Willd.) is a species that presents considerable economic importance, due to its high potential for the wood, cosmetic and medicinal market, adding up economic and environmental value. The control of fungi in stored seeds, as well as the overcoming of dormancy, is fundamental to obtain healthy and uniform seedlings. In this sense, two experiments were carried out with mulungu seeds, aiming to evaluate the effect of atmospheric plasma on inactivation of fungi, as well as a method of overcoming dormancy in seeds of this species. In the first experiment, inactivation of fungi on the surface of E. velutina seeds and in the isolated fungal colonies was evaluated. For this, discharge plasma by dielectric barrier (DBD) was used, via pulses of voltage of 9 kV, repeated in frequency of 640 Hz, with helium (He) and atmospheric (Air) gases. For the second experiment, physiological and germinative response of seeds after pretreatment with the plasma was verified. Seeds were immersed in plasma for 3, 6, and 9 minutes and for purpose of comparison, seeds without treatment (control) and seeds scarified in the opposite side of micropyle were used. Atmospheric plasma reduced the incidence of fungi Aspergillus niger, Aspergillus flavus, Fusarium sp., Brachysporium sp. and Rhizopus sp. in E. velutina seeds. When spores were isolated, plasma reduced formation of fungal colonies. Regarding the application of plasma to overcome dormancy, there were no significant differences when compared to untreated E. velutina seeds